EFEKTIFITAS REBUSAN SIMPLISIA DAUN BINAHONG TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU NIFAS - Faiza, Eva Inayatul (STIKES ADVAITA MEDIKA TABANAN, 2025)
Background: Perineal wounds occur due to excessive and sudden stretching of the birth canal when the fetus is born due to the size of the fetus' head or shoulders or the size of the large child. One way to speed up the healing of perineal wounds is by consuming a simplicia decoction of binahong leaves. Objective: This study aims to determine the effectiveness of consuming simplicia decoction of binahong leaves among postpartum women in healing perineal wounds at the RRJ Ubu Riri Community Health Center, Katikutana District, Central Sumba Regency.Method: This research uses a Quasi-experimental research design with a Nonequivalent Control Group Design. The research population was 30 postpartum mothers who experienced perineal wounds, the sampling technique used total sampling and the research sample was 30 respondents who were divided into 2 groups, namely 15 people in the treatment group and 15 people in the control group. The data collection technique uses an instrument in the form of a perineal wound observation sheet. The data analysis method used is the Mann-Whitney test. Results: Most of the 9 (60.0%) respondents from the treatment group who consumed simplicia decoction of binahong leaves experienced good category of perineal wound healing and almost all 13 (86.7%) respondents from the control group experienced poor category of perineal wound healing. The results of the Mann-Whitney test prove that giving simplicia decoction of binahong leaves is effective in healing perineal wounds in postpartum mothers at the RRJ Ubu Riri Health Center, Kec. Katikutana, Kab. Central Sumba obtained a p value = (0.000) < (0.05). Conclusion: There was a significant difference in perineal wound healing in the treatment group consuming binahong leaf simplicia decoction and the control group, where perineal wound healing in the group consuming binahong leaf simplicia decoction healed faster. With this research, it is hoped that the public can utilize binahong leaf decoction as an alternative that can be used to heal perineal wounds. Keywords: Postpartum; Perineal Wounds; Binahong leaves